2020
DOI: 10.3390/molecules26010092
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Targeting the Mitochondria in Cancers

Abstract: There are abundant sources of anticancer drugs in nature that have a broad prospect in anticancer drug discovery. Natural compounds, with biological activities extracted from plants and marine and microbial metabolites, have significant antitumor effects, but their mechanisms are various. In addition to providing energy to cells, mitochondria are involved in processes, such as cell differentiation, cell signaling, and cell apoptosis, and they have the ability to regulate cell growth and cell cycle. Summing up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 173 publications
1
26
0
Order By: Relevance
“…In recent years, with the development of scientific research technology, countries are paying more and more attention to the research and development of new natural products, and the research and development of natural products has shown a rapid growth trend ( 13 ). According to relevant information, natural products research hotspots focus on plants, animals and microorganisms on land and in the sea, involving a variety of components including proteins, peptides, amino acids, alkaloids and antibiotics ( 14 , 15 ).…”
Section: Pharmacological Effects Of Natural Products Against Cancermentioning
confidence: 99%
“…In recent years, with the development of scientific research technology, countries are paying more and more attention to the research and development of new natural products, and the research and development of natural products has shown a rapid growth trend ( 13 ). According to relevant information, natural products research hotspots focus on plants, animals and microorganisms on land and in the sea, involving a variety of components including proteins, peptides, amino acids, alkaloids and antibiotics ( 14 , 15 ).…”
Section: Pharmacological Effects Of Natural Products Against Cancermentioning
confidence: 99%
“…Several drugs used in cancer treatment are natural products or derivatives of them, such as taxol, isolated from Taxus baccata and the analogs docetaxel (Taxotere) and cabazitaxel (Jevtana) in addition to vincristine and vinblastine (Velban) derived from Catharanthus roseus and their analogues vindesine (Eldisine) and vinorelbine (Navelbine) [ 3 , 4 ]. In addition, of 175 molecules approved for antitumor therapy between 1940 and 2014, approximately 50% were derived from natural products or their derivatives [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yue Yang et al, in 2020, have listed these molecules as diverse as terpenoids (lupeol, betulinic acid), flavonoids (including flavones, isoflavones, flavanols, flavonols, and anthocyanidins), saponins (gracillin, polyphyllin I), alkaloids (codeine, morphine), coumarins (dentatin), quinones (plumbagin) or ichtyotoxins (rotenone). Various molecular processes are impacted by these natural substances, including generation of ROS, eventually leading to dysfunctions as decreased respiration and therefore ATP production, mitochondrial hyperfission, release of cytochrome c and subsequently activation of caspases and apoptosis [ 1 ]. Most of these molecules may have transient effects because they are metabolized by the cells and therefore deactivated.…”
Section: Introductionmentioning
confidence: 99%